THE HALO IMAGE IN THE ARTISTIC DECORATION OF THE URARTIAN MEDALLIONS - Погосян, Гаяне Робертовна (History, Archeology and Ethnography of the Caucasus, 2025)
Abstract. Urartian medallions have been found at Karmir-Blur (Red-Hill, Teyshebaini, Armenia), Toprak-Kale (Rusakhinili, Turkey), Çavushtepe (Haykaberd, Turkey), Giyimli (Hirkanis, Turkey) and other sites. The relevance of this article lies in the fact that it attempts to study and analyze for the first time the iconography and symbolism of divine halo (nimbus) image in the artistic decoration of some medallions. The issue lies in the fact that most researchers attribute the origin of the halo to the ancient Persian culture, but associated with the idea of the sun or divine light was used in the sacred images of the ancient Armenian Highlands much earlier.
Keywords: Keywords; Urartu (the Kingdom of Van); medallion; halo; Haldi; ritual; iconography; symbol.